Pengaruh Konfigurasi Politik Hukum Orde Baru terhadap Kompilasi Hukum Islam (KHI) di Indonesia - Muslim, Mochammad (Prodi Siyasah Jinayah (Hukum Tata Negara dan Hukum Pidana Islam) Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2014)
Abstract: This article discusses the influence of legal political configuration of the New Order against the Compilation of Islamic Law in Indonesia. Legal political configuration of the New Order was based on Pancasila and the Constitution of 1945 as the basis of its policy to enhance and improve national law. The background formation of KHI is the need for technical justicial Religious Courts. KHI can be regarded as Indonesian fiqh sound Pancasila due to the influence of political codification and unification of the law of the New Order. This study efforts to prove that the relationship between the political configuration and character of legal product that produces any legal products is a reflection of the political configuration that gave it birth. The character of the law product is determined by the political vision that developed in the midst of society. Sometimes the character of legal product is responsive/populistic and there is also a legal product was characterized by conservative/orthodox/elitist. Likewise with KHI must have certain characters were born as a result of legal political configuration of the New Order regime.Keywords: Effect, political configuration, the new order, and KHI